How microbiota composition and diversity are related to striatal volumes in early life - Bourzeix, Marie (My University, 2021)
A primary goal of gut-brain research is to understand how human gut microbiota affects mental health such as cognition or neuropsychiatric disorders. Studies employing rodent models reported that gut microbiota had a strong influence on neurodevelopment, especially during the critical period of ‘developmental programming’, which seems to be a key window for external influences. However, knowledge of the origins of the relationship between gut-microbiota and brain functions is still limited due to the scarcity of the human gut-brain studies, particularly those focusing on infant populations. Deep brain structures, in particular subcortical structures such as the striatum, are major components to the gut-brain axis and also have been shown to have a central role in neurodevelopment. Finally, previous literature demonstrates that the first years of life are critical to neurodevelopment and gastrointestinal colonization. The aim of this thesis is to explore the relationship between the fecal microbiota composition and diversity of 2.5 months infants and the striatum volumes measured at one month. This exploratory cross-sectional study was conducted using data collected on 56 infants drawn from the FinnBrain Birth Cohort study, which focuses on the effects of environmental and genetic stimuli on child development and health. The results showed no statistically significant associations between alpha and beta-diversity, and the striatum volumes. The correlation between alpha-diversity and striatum volumes tended to present visible sex-differences, despite their statistical insignificance. This novel study encourages future longitudinal studies to provide insight into the relationship between characteristics of the gut microbiota and the development of the brain especially during the critical phases of neurodevelopment throughout life.
Keywords: infant, gut, microbiota, gut-brain axis, striatum